Frequent, quantitative bone planar scintigraphy for determination of bone anabolism in growing mice - Zaloszyc, Ariane; Schmitt, Claus P.; Sayeh, Amira; Higel, Laetitia; Gros, Catherine-Isabelle; Bornert, Fabien; Aubertin-Kirch, Gaëlle; Dillenseger, Jean-Philippe; Goetz, Christian; Constantinesco, André; Fischbach, Michel; Bahram, Seiamak; et al. (PeerJ, 2021)
Background To provide insight into bone turnover, quantitative measurements of bone remodeling are required. Radionuclide studies are widely used in clinical care, but have been rarely used in the exploration of the bone in preclinical studies. We describe a bone planar scintigraphy method for frequent assessment of bone activity in mice across the growing period. Since repeated venous radiotracer injections are hardly feasible in mice, we investigated the subcutaneous route. Methods Repeated 99mTc-hydroxymethylene diphosphonate (HMDP) tracer bone planar scintigraphy studies of the knee region and µCT to measure femur growth rate were performed in eight mice between week 6 and week 27 of life, i.e., during their growth period. Three independent investigators assessed the regions of interest (ROI). An index was calculated based on the counts in knees ROI (normalized by pixels and seconds), corrected for the activity administered, the decay between administration and imaging, and individual weights. Results A total of 93 scintigraphy studies and 85 µCT were performed. Repeated subcutaneous tracer injections were well tolerated and allowed for adequate radionuclide studies. Mean scintigraphic indexes in the knees ROI decreased from 87.4 ± 2.6 × 10−6 counts s−1 pixel−1 MBq−1 g−1 at week 6 to 15.0 ± 3.3 × 10−6 counts s−1 pixel−1 MBq−1 g−1 at week 27. The time constant of the fitted exponential decay was equal to 23.5 days. As control mean femur length assessed by µCT increased from 12.2 ± 0.8 mm at week 6 to 15.8 ± 0.2 mm at week 22. The time constant of the fitted Gompertz law was equal to 26.7 days. A correlation index of −0.97 was found between femur growth and decrease of bone tracer activity count between week 6 and 24. Conclusion This methodological study demonstrates the potential of repeated bone planar scintigraphy in growing mice, with subcutaneous route for tracer administration, for quantitative assessment of bone remodeling.